Perl by example - Quigley, Ellie (Prentice Hall, 2008)
"I picked up a copy of JavaScript by Example over the weekend and wanted to thank you for putting out a book that makes JavaScript easy to understand. I've been a developer for several years now and JS has always been the "monster under the bed," so to speak. Your book has answered a lot of questions I've had about the inner workings of JS but was afraid to ask. Now all I need is a book that covers Ajax and Coldfusion. Thanks again for putting together an outstanding book."--Chris Gomez, Web services manager, Zunch Worldwide, Inc. "I have been reading your UNIX ® Shells by Example book, and I must say, it is brilliant. Most other books do not cover all the shells, and when you have to constantly work in an organization that uses tcsh, bash, and korn, it can become very difficult. However, your book has been indispensable to me in learning the various shells and the differences between them ... so I thought I'd email you, just to let you know what a great job you have done!"--Farogh-Ahmed Usmani, B. Sc. (Honors), M. Sc., DIC, project consultant (Billing Solutions), Comverse "I have been learning Perl for about two months now; I have a little shell scripting experience but that is it. I first started with Learning Perl by O'Reilly. Good book but lacking on the examples. I then went to Programming Perl by Larry Wall, a great book for intermediate to advanced, didn't help me much beginning Perl. I then picked up Perl by Example, Third Edition- this book is a superb, well-written programming book. I have read many computer books and this definitely ranks in the top two, in my opinion. The examples are excellent. The author shows you the code, the output of each line, and then explains each line in every example." - Dan Patterson, software engineer, GuideWorks, LLC "Ellie Quigley has written an outstanding introduction to Perl, which I used to learn the language from scratch. All one has to do is work through her examples, putz around with them, and before long, you're relatively proficient at using the language. Even though I've graduated to using Programming Perl by Wall et al., I still find Quigley's book a most useful reference." - Casey Machula, support systems analyst, Northern Arizona University, College of Health and Human Services "When I look at my bookshelf, I see eleven books on Perl programming. Perl by Example, Third Edition, isn't on the shelf; it sits on my desk, where I use it almost daily. When I bought my copy I had not programmed inches